Diagnostics system for manufacturing process problems (DSMPP) - Okfalisa, Okfalisa (2007)
Facing the market competition, fulfilling the customer satisfaction and increasing the product quality in manufacturing firms motivated investigation and diagnosis in their production output failure. To gain correct and accurate diagnostic, the entire process must be recorded and controlled in every step of manufacturing. In this project, a prototype system has been developed to record the knowledge base that was used to diagnose the source of tiles defects and to recommend action to solve the problems. This system consists of two main components, the knowledge base component and the inference engines. The knowledge base has been developed by analyzing the data and information that is related to the tiles defect, such as symptoms, probable causes, types of defect, processes, sub processes, tile classifications and recommended actions. On the other hand, the inference engines has been built by implementing the forward chaining method to root the causes of defect and depth first search in searching procedures. The analysis proves that this system can help workers in the company to diagnose tiles defect and solve problems regarding the defect. Besides that, the system can also help share and transfer knowledge among knowledge workers in manufacturing firm.